Behavior of Full-Scale One-Way Semi-Precast Concrete Slabs with Varying Sizes and Shear Connectors - Z. Naser, Kadhim; A. Al-Gusab, Hussein; Z. Thamer, Ansam; A. Almayah, Abdulamir; Sh. Mahdi , Muthana; D. Abdullah, Mazin (Salehan Institute of Higher Education, 2025)
This study investigates the structural performance of semi-precast concrete slabs (SPCSs), an innovative hybrid construction system that integrates factory-produced precast concrete units with a cast-in-place (CIP) concrete topping to create a composite structural element. This system offers notable advantages in terms of construction acceleration, improved quality control, and reduced labor requirements, as the precast unit serves as both a load-bearing component and a permanent formwork. To evaluate the structural behavior of the SPCSs, an experimental program was conducted on seven full-scale, one-way slab specimens with varying span lengths (4.75 m and 6.0 m), precast unit thicknesses (80 mm and 100 mm), and shear connector geometries (rectangular and triangular). A control slab without shear connectors was also tested to establish a baseline for comparison. The results demonstrated that the inclusion of shear connectors significantly enhanced structural performance. Specifically, the ultimate load capacity increased by 186.4%, and the cracking load increased by 220% compared to the control specimen. Rectangular connectors proved more effective than triangular ones in minimizing interface slip and enhancing ductility. The initial stiffness increased by 163.95%, while the energy dissipation capacity improved by 411.35%. Although variations in span length and topping thickness had relatively minor effects, the presence and geometry of shear connectors played a decisive role in ensuring effective composite action. All reinforced slabs exhibited flexural failure modes, indicating strong bonding and interaction between the precast and cast-in-place (CIP) concrete layers, whereas the control slab experienced premature failure due to interlayer debonding. Theoretical equations based on ACI 318-19 were used to estimate the nominal flexural capacities of the hybrid SPCS slabs, showing reliable agreement with the experimental results. These findings demonstrated the importance of shear connector design in maximizing the load-bearing capacity, ductility, and structural stiffness of SPCS systems under both service and extreme loading conditions.